Frequency and characteristics of adverse events caused by anti-tuberculosis drugs in pulmonary tuberculosis patients with diabetes myelitis - O. G. Komissarova; R. Yu. Аbdullaev; S. V. Aleshina (Туберкулез и болезни лёгких)
The objective: to study the frequency and nature of adverse events caused by anti-tuberculosis drugs in pulmonary tuberculosis patients with and without concurrent diabetes mellitus.Subjects and methods. 396 patients with pulmonary tuberculosis were examined: 203 patients who had diabetes were included in the TB + diabetes group; the TB group consisted of 193 patients with pulmonary tuberculosis without diabetes.Results. The incidence of adverse events caused by anti-tuberculosis drugs was analyzed and compared in both groups. Thus, in the TB+diabetes group adverse events developed in 146/203 (71.9%) patients and in 62/193 (32.1%) patients in the TB group ( p < 0.01). Hepatotoxic reactions prevailed in both groups, but in the TB + diabetes group, they were statistically significantly more frequent versus the TB group (55.2 and 27.4%, respectively; p < 0.01). Also, allergic reactions (20.7 and 6.2%, respectively; p < 0.01) and neurotoxic events (13.3 and 5.1%, respectively; p < 0.01) were statistically significantly more frequent in the TB + diabetes group compared to the TB group.